A cross-sectional study on burden of disability among leprosy patients in a tertiary care center of West Bengal, India - Shibasish Banerjee; Chinmay Nandi; Soumitra Mondal; Kaushik Mitra (Asian Journal of Medical Sciences, 2022)
Background: Leprosy, an infectious disease caused by Mycobacterium leprae, mainly affects skin, peripheral nerves, mucosa of the upper respiratory tract, and eyes. New goal of the WHO is to decrease the rate of disabilities in new cases among 10 lakhs population 35% with compare to base line 2010. Burden of disabilities continues to rise in society and they are in need of prevention and/or rehabilitation services. Prevention of disability consists of early detection and treatment of reactions and nerve damage. Aims and Objectives: The objectives of the study were to find out the proportion of disability among leprosy cases and the factors associated with disability. Materials and Methods: This observational, cross-sectional, and descriptive study was conducted at Dermatology, Venerology, and Leprosy Department of a tertiary hospital from May 2015 to January 2016. Data were collected from all the study population by interviewing the study subjects and clinical examination of patients with pre-designed and pre-tested schedule and disability assessment form available from National leprosy eradication program (NLEP). Skin examination was done as per NLEP guideline and palpation of all the nerve and function of the nerve by voluntary muscle testing (VMT) done as stated national guideline. Data were analyzed using R Studio. Results: Among the study population, 87.9% of patients had disability and 61.7% of patients had Grade 2 disability. EHF score of most of the patients (59.8%) was ranged between 4 and 6. Among participants 33.6% had foot ulcer, 28% had ulnar claw hand, and 15.6% had lagophthalmos. Proportions of the upper limb digit loss, median claw hand, wrist drop, foot drop, and lower limb digit loss were 5.6%, 13.1%, 3.7%, 9.3%, and 12.1%, respectively. Conclusion: The present study reflected that a large number of cases with leprosy have presented with complication and disability. There was significant association of disability with multibacillary cases, number of nerve thickening, and number of functionally impaired nerve as assessed by VMT, lepra reaction, presence of nodular skin lesion and patch in skin and delayed initiation of treatment since the onset of symptoms.